Peran Pendidikan Islam Dalam Menghadapi Tantangan Di Era Globalisasi - Fudhla, Mahmudatun (Maliki Interdisciplinary Journal, 2024)
The role of Islamic education has important significance in facing challenges in the era of globalization. Globalization brings rapid changes in various aspects of life, including culture, technology and economics, which can have an impact on traditional values and Islamic identity. Education is considered key to overcoming the negative impacts of globalization, especially related to easy access to dangerous content on the internet. Learning Islamic character, morals and ethics is important in facing the challenges of globalization. Islamic education must also adapt to global changes, including curriculum updates, diversification of learning materials, and the use of technology. The challenges faced by Islamic education include moral crises, personality, and the negative impact of globalization. Therefore, Islamic education plays a major role in shaping the character of Muslims so they are able to face these challenges.